2020
DOI: 10.1080/09638237.2020.1770206
|View full text |Cite
|
Sign up to set email alerts
|

Peer-led groups for survivors of sexual abuse and assault: a systematic review

Abstract: Background: There are current concerns about whether appropriate support is provided for sexual abuse and assault survivors. We reviewed the published evidence for peer-led groups in the care of survivors. Aims: To determine the health and wellbeing outcomes of peer-led, group-based interventions for adult survivors who have experienced sexual abuse and assault and describe the experiences of participants attending these groups. Method: Systematic review. The following databases were searched: Medline, PsycINF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…While there is little research about peer services for victim-survivors of sexual violence and abuse ( Konya et al, 2020 ), much related research is underway within the mental health field. A recent systematic review, for example, describes the plethora of current research, and indicates disparities between different forms of peer support in terms of outcome, and variations in effectiveness dependent on the particular outcomes measured ( White et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is little research about peer services for victim-survivors of sexual violence and abuse ( Konya et al, 2020 ), much related research is underway within the mental health field. A recent systematic review, for example, describes the plethora of current research, and indicates disparities between different forms of peer support in terms of outcome, and variations in effectiveness dependent on the particular outcomes measured ( White et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, focusing on peer group support for victim-survivors of sexual violence and abuse, we reported that group participants experienced several benefits from peer support. These included: experiencing empathic witnessing resulting in feeling genuinely understood; finding permission to acknowledge and accept the reality of experiences; increased social connectedness; impetus towards healing from witnessing others’ progress; and opportunities to discover resources and coping strategies ( Konya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peer support is about giving and receiving help, which helps people understand one another because they share a similar experience, and it can model a willingness to grow and learn. Through this, new contexts are created which offer peers new ways of thinking about their victimization experience (see also Hardy et al, 2019 in Ali & Lucock, 2020; Konya et al, 2020; Cross, 2019; NHS, 2016 in Gregory et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The recognition and understanding between peers offer opportunities to validate reactions and behaviors and can make them feel more at ease with their own situation. Moreover, this process of normalization and the space created by peers to share thoughts and feelings diminishes the sense of isolation and feelings of guilt (Carey & MSW, 1999; Cross, 2019; Feigelman & Feigelman, 2008; Finn & Lavitt, 1994; Gregory et al, 2021; Hundt et al, 2015; Knight, 1990; Konya et al, 2020; van de Ven, 2020). Yalom (1985 in Knight, 1990) referred to this as ‘universality’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation